Comparação entre adenosina e óxido nítrico para a realização de teste de vasorreatividade pulmonar em pacientes com hipertensão arterial pulmonar - Edmundo Clarindo Oliveira (2010)
The evaluation of pulmonary vasoreactivity is recommended in order to better define the therapeutic option in all forms of pulmonary arterial hypertension (PAH). Several drugs have been used for this evaluation. Inhaled nitric oxide (ONi) is considered to be the best option, even though it is not available in most health service centers in Brazil. Adenosine has a well-known pulmonary vasodilation action, is easily available, has a half life of a few seconds, and some papers suggest it should be used to perform pulmonary vasoreactivity tests. The aim of this study is to compare the use of the two drugs in these tests. The study included 39 patients aged from 2 to 69 years old (medium age = 44), 82% of whom were female patients. Hypertension was classified, according to its etiology, as idiopathic in 26 patients (66.7%), schistosomal in 4 patients (10.2%), congenital cardiopathy in 3 patients (7.7%), pulmonary thromboembolism in 2 patients (5.1%) and collagen disease in 4 patients (10.2%) and, according to its severity, as light in 8 patients (20.5%), moderate in 13 patients (33.3%) and severe in 18 patients (46.2%). The measurements were made in basal state, with ONi, and after continuous infusion of adenosine in the pulmonary artery. ONi was started with 10 ppm, increasing 10 ppm every 5 minutes, till a response was obtained or 80 ppm were reached. Adenosine was started with 50 g/kg/min, increasing 50 g/kg/min every 5 minutes, till either 500 g/kg/min, or a positive response or side effects were reached. The criteria for a positive response were: 1) a reduction of 10 mmHg in the medium pulmonary pressure, associated to a final value below 40 mmHg, with the maintenance or increase in the systemic debit in the non-cardiac forms; and 2) an increase in the QP/QS relationship above 1.8, associated to a reduction in the relationship RP/RS higher than 30% in the congenital heart disease. For the statistical analysis the comparison between measurements at maximal dose versus basal state during each vasodilator challenge and between challenges was performed using student t test for paired samples. Data concerning categorical variables were expressed as proportions and were compared by McNemar test for paired samples. A p<.05 value was considered significant. The sample size was calculated using the software Study Size v. 2.0.2 (Västra Frölunda, Sweden). After a pilot study of 20 patients without any positive response to adenosine, the sample size was recalculated. Considering paired observations, alpha value of 0.05, beta values of 0.8, and 2% of response to adenosine and 20% to iNO, a sample size of 39 patients was obtained. Out of the 39 individuals included in the study, 6 (15.4%) presented a positive response to the TRP with nitric oxide, without side effects. Four of these patients were part of the 26 individuals group diagnosed with HAPI (15.4%), and the other two were part of the 13 individuals group with other forms of HAP (15,4%). The comparison of the homodynamic measurement in basal state and after maximum achieved dose of the adenosine and nitric oxide showed response with ONi in 6 of the 39 patients and absence of response with adenosine (McNemar test, p = 0.047). The medium doses of adenosine was 301 g/kg/min and 23/39 patients (58.9%) did not reach the maximum dose due to side effects: 7 (17.9%) presented bronchospasm; 5 (12.8%) thoracic pain; 3 (7.7%) bradycardia; 6 (15.4%) bronchospasm and thoracic pain; and 2 (5.1%) bradycardia and bronchospasm. Our results show that adenosine should not be used to do pulmonary vasoreactivity tests in patients with pulmonary hypertension.